2016
DOI: 10.1021/acs.biochem.6b00733
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid and Efficient Assay for the Characterization of Substrates and Inhibitors of Nicotinamide N-Methyltransferase

Abstract: Nicotinamide N-methyltransferase (NNMT) is one of the most abundant small molecule methyltransferases in the human body and is primarily responsible for the N-methylation of the nicotinamide (vitamin B3). Employing the cofactor S-adenosyl-l-methionine, NNMT transfers a methyl group to the pyridine nitrogen of nicotinamide to generate N-methylnicotinamide. Interestingly, NNMT is also able to N-methylate a variety of other pyridine-containing small molecules, suggesting a secondary role for the enzyme in the det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
65
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 23 publications
4
65
3
Order By: Relevance
“…N 1 -Methylnicotinamide (1-methylnicotinamide, 1-methylpyridin-1-ium-3carboxamide) is a product of tryptophan and niacin metabolism (Fukuwatari et al, 2004;Menon et al, 2007;Hiratsuka et al, 2014). It is synthesized from nicotinamide by cytosolic nicotinamide N-methyltransferase (NNMT) using S-adenosyl-L-methionine as methyl donor (Rini et al, 1990;Aksoy et al, 1994;van Haren et al, 2016) and is then further metabolized by cytosolic aldehyde oxidase to two metabolites, N 1 -methyl-2-pyridone-5carboxamide (2-Py) and N 1 -methyl-4-pyridone-3-carboxamide (4-Py) (Kitamura et al, 2008). Both enzymes are predominantly expressed in the liver, but localization to other tissues, including the kidney, has been reported (Aksoy et al, 1994;Smith et al, 1998;Nishimura and Naito, 2006).…”
Section: Biomarkers For Function Of Renal Cation Transporters (Orgmentioning
confidence: 99%
“…N 1 -Methylnicotinamide (1-methylnicotinamide, 1-methylpyridin-1-ium-3carboxamide) is a product of tryptophan and niacin metabolism (Fukuwatari et al, 2004;Menon et al, 2007;Hiratsuka et al, 2014). It is synthesized from nicotinamide by cytosolic nicotinamide N-methyltransferase (NNMT) using S-adenosyl-L-methionine as methyl donor (Rini et al, 1990;Aksoy et al, 1994;van Haren et al, 2016) and is then further metabolized by cytosolic aldehyde oxidase to two metabolites, N 1 -methyl-2-pyridone-5carboxamide (2-Py) and N 1 -methyl-4-pyridone-3-carboxamide (4-Py) (Kitamura et al, 2008). Both enzymes are predominantly expressed in the liver, but localization to other tissues, including the kidney, has been reported (Aksoy et al, 1994;Smith et al, 1998;Nishimura and Naito, 2006).…”
Section: Biomarkers For Function Of Renal Cation Transporters (Orgmentioning
confidence: 99%
“…22 We were therefore interested in assessing whether such a strong binding, slowly converted NNMT substrate might in fact act as an inhibitor by occupying the NNMT active site. 16,22 Indeed, it was found that norharmane inhibits NNMT with an IC 50 of 115.3 ± 20.6 µM. The low K M is offset by a diminished turnover rate giving norharmane the ability to occupy the NNMT active site and effectively block the methylation of nicotinamide.…”
Section: Articlementioning
confidence: 99%
“…To assess NNMT inhibition, we used an assay recently developed in our group. 16 This assay employs Ultra High Performance (UHP) Hydrophilic Liquid Interaction Chromatography (HILIC) Quadrupole Time-Of-Flight Mass Spectrometry (QTOF-MS) to rapidly and efficiently measure NNMT activity. Using this method, we previously determined the IC 50 values for the general methyltransferase inhibitors sinefungin and AdoHcy and here demonstrate that it can be used for the evaluation of new NNMT inhibitors.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the serum levels of NNMT were significantly increased in patients with colorectal, lung and renal cell carcinoma compared with those in the control group (10,14,15). Previous studies have also demonstrated that the upregulation of NNMT is associated with poor prognosis, advanced tumor stage, tumor cell migration and invasion (9,16,17). Although, overexpression of NNMT has been identified in gastric cancer (18), the underlying molecular mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 97%